The Evaluation of the Quality of Local Water Company Tirta Anoa Processed Water in the Community of West Kendari District, Kendari City - Rusdhan, Muhammad; Azizi Jayadipraja, Erwin; Harun, Aziz (Magister Kesehatan Universitas Mandala Waluya, 2024)
Backgrounds: The government has the task of collecting, purifying and distributing clean water from water terminals via water channels, pipes or tank cars (in administrative management units with economic activities) to homes, industrial companies or other commercial uses. For this reason, Local water company has the responsibility to provide clean water for all groups of people in an area. Methods: This type of research is observational research with a descriptive approach to get an overview of the quality of Local water company Tirta Anoa's processed water. Water quality sampling was carried out in 9 sub-districts in West Kendari District, which is the sub-district with the largest population of 44,290 people. Results: The results of the pollution index analysis for TDS parameters show that river waters in the study study area at 7 monitoring points are still classified as meeting water quality standards, namely still below 1,000 mg/L. The highest TDS content was found at station 5 (AB.03 = 611 mg/L) and station 6 (AB.04 = 614 mg/L), while the lowest TDS value was at station 2 (AB.02 = 193 mg/L). And the concentration of TSS parameters is still below the quality standard, namely monitoring point 1 (AP.01 to 5 (AB.05) respectively 4.7 mg/L; 3.4 mg/L; 2.6 mg/L ; 3.7 mg/L; 3.9 mg/L; Conclusion: There is water quality (physics, chemistry, biology) from Local water company Tirta Anoa processed water which has been consumed by the community in West Kendari.